Construction lamellar BaFe12O19/Bi3.64Mo0.36O6.55 photocatalyst for enhanced photocatalytic activity via a photo-Fenton-like Mo6+/Mo4+redox cycle. (November 2022) - Zhang, Tingting; Zhou, Puyang; Zhang, Lingxiao; Xia, Changkun; Xie, Meng; Guo, Qiting; Chen, Min; Yuan, Junjie; Li, Xiang; Xu, Yuanguo
Abstract: The novel BaFe12 O19 /Bi3.64 Mo0.36 O6.55 composite materials were constructed as magnetically recyclable photo-Fenton-like degradation systems. The composite catalyst not only promoted the effective transfer of photo-generated electrons and improved the Mo 6+ /Mo 4+ cycle consequent, but also activated hydrogen peroxide to generate oxidizing free radicals. BaFe12 O19 /Bi3.64 Mo0.36 O6.55 –0.25 exhibited an outstanding degradation performance for tetracycline hydrochloride it is 1.3 times to Bi3.64 Mo0.36 O6.55 . The thermal catalytic performance of the Bi3.64 Mo0.36 O6.55 monomer is similar to that of the BaFe12 O19 /Bi3.64 Mo0.36 O6.55 material without light. However, the removal rate of BaFe12 O19 /Bi3.64 Mo0.36 O6.55 material reaches 84.5% after 60 min with light, far exceeding that of Bi3.64 Mo0.36 O6.55 material. By way of the contrast experiment with light and without light, it is further demonstrated that interfacial interaction between BaFe12 O19 and Bi3.64 Mo0.36 O6.55 acted a key role in the photocatalytic reaction system. It is also a good advantage that pollutants can be efficiently degraded without adjusting the pH. The characterization of photocurrent and X-ray photoelectron spectroscopy (XPS) also further proved the synergy between the two materials, which is useful to the separation of electrons and holes. The synergy ultimately improves the degradation performance. Besides, BaFe12 O19 /Bi3.64 Mo0.36 O6.55 can be easily separated by an external magnetic field after the photocatalytic activity reaction owing to BaFe12 O19 's magnetic properties. It provides a new research idea for the construction and iron-based heterogeneous Fenton-like system for magnetic degradation of antibiotics. Graphical abstract: Image 1 Highlights: The composite was constructed as magnetically recyclable degradation system. BaFe12 O19 /Bi3.64 Mo0.36 O6.55 can degrade dyes and antibiotics in H2 O2 /vis system. Exploring the main factors influence the performance of photo-Fenton system. According to ESR, .OH 、 O2 - and electron-hole pairs are the main active species.